Impact of the Number of Administered Systemic Treatment Lines on Local Response to Radiation Therapy for Multiple Myeloma - Andrea Emanuele Guerini, MD; Eneida Mataj, MD; Paolo Borghetti, MD; Luca Triggiani; Ludovica Pegurri, MD; Stefania Nici; Stefano Riga; Alessandra Tucci, MD; Angelo Belotti, MD; Marco Lorenzo Bonù, MD; Giorgio Facheris, MD; Stefano Maria Magrini; et al. (Advances in Radiation Oncology)
Purpose: Multiple myeloma (MM) tends to develop resistance to systemic therapy through multiple mechanisms that might as well induce radioresistance, as suggested by preclinical studies. The aim of the present analysis was to elucidate whether the number of systemic treatment lines received prior to radiation therapy (RT) might confer radioresistance and influence local response. Methods and Materials: This single-center retrospective study enrolled patients who received RT for MM at our institution between January 1, 2005, and January 31, 2023. Information regarding RT, systemic therapy, and characteristics of the patients and disease were retrieved from medical records. The primary outcome for this analysis was radiologic local response at 6 months after RT, according to RECIST 1.1 (Response Evaluation Criteria in Solid Tumors) or PERCIST 1.0 (Positron Emission Tomography Response Criteria in Solid Tumors) criteria. The secondary outcome was toxicity reported during the RT course. Results: Data from 665 MM lesions from 366 patients were analyzed. Data regarding local response at 6 months were available for 217 lesions, reporting 29 complete responses (13.4%), 141 partial responses (65%), 42 stable diseases (19.4%), and only 5 disease progressions (2.3%). The number of previous systemic treatment lines had no impact on radiologic response at 6 months (p = .721). RT BED10 (Biologically Effective Dose) had a significant impact on response at 6 months (p = .007). The toxicity profile was optimal, as grade > 2 events during RT were reported only in 0.9% of cases. Conclusions: In this large retrospective cohort of MM patients, the number of systemic treatment lines administered before RT had no impact on the local response, confuting concerns of cross-resistance raised by multiple preclinical studies. Disease control after RT was optimal, and instances of severe toxicities during treatment were rare.